The change in circulating galectin-3 predicts absence of atrial fibrillation after thoracoscopic surgical ablation. Issue 5 (19th May 2017) - Berger, Wouter R; Jagu, Benoît; van den Berg, Nicoline W E; Chan Pin Yin, Dean R P P; van Straalen, Jan P; de Boer, Onno J; Driessen, Antoine H G; Neefs, Jolien; Krul, Sébastien P J; van Boven, WimJan P; van der Wal, Allard C; de Groot, Joris R
Abstract: Aims: Galectin-3 (Gal-3) is an important mediator of cardiac fibrosis, particularly in heart failure. Increased Gal-3 concentration (Gal-3), associated with increased risk of developing atrial fibrillation (AF), may reflect atrial fibrotic remodelling underlying AF progression. We aimed to investigate whether the change in serum Gal-3 reflects alterations of the arrhythmogenic atrial substrate following thoracoscopic AF surgery, and predicts absence of AF. Methods and results: Consecutive patients undergoing thoracoscopic AF surgery were included. Left atrial appendages (LAAs) and serum were collected during surgery and serum again 6 months thereafter. Gal-3 was determined in tissue and serum. Interstitial collagen in the LAA was quantified using Picrosirius red staining. Ninety-eight patients (76% male, mean age 60 ± 9 years) underwent thoracoscopic surgery for advanced AF. Patients with increased Gal-3 after ablation compared to baseline had a higher recurrence rate compared to patients with decreased or unchanged Gal-3 (HR 2.91, P  = 0.014). These patients more frequently had persistent AF, longer AF duration and thick atrial collagen strands ( P  = 0.049). At baseline, Gal-3 was similar between patients with and without AF recurrence: 14.8 ± 3.9 µg/L vs. 13.7 ± 3.7 µg/L, respectively in serum ( P  = 0.16); 94.5 ± 19.4 µg/L vs. 93.3 ± 30.8µg/L, respectively in atrial myocardium ( P  = 0.83). There was no correlation between serum Gal-3 and left atrial Gal-3 ( P  = 0.20), nor between serum Gal-3 and the percentage of fibrosis in LAA ( P  = 0.18). Conclusion: The change of circulating Gal-3, rather than its baseline value, predicts AF recurrence after thoracoscopic ablation. Patients in whom Gal-3 increases after ablation have a high recurrence rate reflecting ongoing profibrotic signalling, irrespective of arrhythmia continuation.